The Influence of Technology Based Learning Facilities to Student Learning Achievement - Muhamad Havid Abdul Aziz; Agus Efendi; Basori Basori (Journal of Informatics and Vocational Education, 2019)
Education is very important for us, the country can go forward because the people are educated. The success of education is determined by the quality of education itself. To know the quality of education required a result or achievement. One of the factors affecting achievement is the facility. The purpose of this study is to determine whether there is influence of learning facilities on student achievement. Sampling using simple random sampling system as much as 58 people from the total population as much as 70 people at the level of formal education. The method used in data collection that is using quisioner, observation and documentation. Data analysis technique used is using simple linear regression analysis. Based on the results of data analysis and hypothesis testing it is known that the two variables of learning facilities (X) and student learning achievement (Y) have a positive influence, this is evidenced by r = 0.277 where the guidelines used to provide interpretation proposed by Sugiyono are at intervals 0.20 - 0.399 which fall into the low category[18]. Based on the results of research that has been put forward by the authors which there is influence between learning facilities on learning achievement with low categories, it is necessary to improve the effectiveness of the use of learning facilities and conducted other research on other factors that affect student achievement in addition to learning facilities.